Development of an E-book based on Multimode Representation and Technological Pedagogical and Content Knowledge (TPACK) - Masrifah Masrifah; Agus Setiawan; Parlindungan Sinaga; Wawan Setiawan (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
This research aimed to develop an e-book for physics teachers based on multimode representation and Technological Pedagogical and Content Knowledge (TPACK)Thus, it was expected to improve pedagogical, professional, and ICT literacy competencies have been carried out. This research employed Educational Research and Development (R&D) by Borg and Gall, but the steps were limited only to the initial product revision. The instrument used was a questionnaire to evaluate the quality and understanding of the e-book. This study involved five expert validators in pedagogy, IT, and physics content. After the e-book draft was validated and revised, it was tested on a limited basis to 16 in-service physics teachers and eight pre-service teachers. The development eligibility of the e-book for physics teachers was seen from the results of the quality and readability tests of the content. The results of the expert validation regarding the quality of the developed e-book are in the excellent category with an average percentage of 88%. The test results show that the average percentage of physics teachers’ e-book understanding is 80.3%. The test results conclude that the multimode and TPACK-based e-books developed for high school physics teachers are feasible to apply. However, it should be tested more extensively before being used further in the learning process.